Trace Element: A Focus on Zinc in Humans - Pathak, Vishal; Ahuja, A.; R. singh, miss; Pathak, Prabhat (Asian Journal of Chemistry, 2010)
Zinc is a nutritional imperative during periods of rapid tissue growth. Tissues with high cellular turnover including skin, gastrointestinal mucosa, spermatogonia, etc. are characteristically affected. Zinc deficiency should be identified in any case of obscure retarded growth or infertility associated with the characteristic rash. A distinctive rash most often around eyes, nose, mouth, impaired taste and smell, poor appetite, mental lethargy are the essential features of zinc deficiency.